Peran Ibu Rumah Tangga dalam Meningkatkan Perekonomian Keluarga melalui Home Industri Lemang Tapai di Desa Ulak Lebar - Piter Martin Colindri; Romi Adetio Setiawan; Anwar Junaidi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the role of housewives in enhancing family economic well-being through the lemang tapai home industry in Pekan Masat, Ulak Lebar Village, and to examine this activity from the perspective of Islamic economics. The study employs a qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that the involvement of housewives in the lemang tapai industry contributes to increasing family income, which is used to cover basic needs, children's education, and health. Furthermore, housewives are able to balance their roles between economic activities and domestic responsibilities. From the Islamic economic perspective, lemang tapai business activities are permissible as long as they do not violate sharia principles. The study concludes that the involvement of housewives in the lemang tapai home industry plays a significant role in enhancing family welfare.